Doing digital methods - Rogers, Richard (Thousand Oaks : Sage Publications, 2024)
"Teaching the concrete methods needed to use digital devices, search engines and social media platforms to study some of the art in researching the natively digital. With explanation of context and techniques and a rich set of case studies, Richard Rogers teaches you how: Build a URL list to discover internet censorship Transform Google into a research machine to detect source bias Make Twitter API outputs comprehensible and tell stories Research Instagram to locate 'hashtag public' Extract and fruitfully analyze Facebook post, images and video And locate much, much more"
Keywords: Internet research; Internet searching; World Wide Web -- Research; Social Media -- Research; Internet -- Social aspects